Scientific dissemination and education: the biogeography in science museums - Padoan, Lucas de Lima Fernandes; Vasconcelos, Leonardo de Souza (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
This work aims to recognize the Museums of science as a major impetus with regard to scientific dissemination, a social role that is indispensable for the dissemination of knowledge that is produced within the academy. That said, this study was concerned to undertake a concise historical reconstruction of biogeographic thought, highlighting the importance of science museums as a complementary bibliography for studies and lessons fields. Thus, we exemplify with Museu de História Natural e Jardim Botânico da UFMG (MHNJB/UFMG), Museu de Ciências Naturais da Pontifícia Universidade Católica (MCN/PUC-MG) and Espaço do Conhecimento UFMG (ECU) as important spaces for Science dissemination. Finally, we propose that museums are used as places of work camps, whether by schools or colleges, not only encouraging research by students, but also encouraging them to get to know new cultural spaces.